Policy dialog workshop on flood index insurance and drought management for agricultural development in Bihar, India - International Water Management Institute (International Water Management Institute, 2017)
Climate variability already poses a significant threat to humanity, with the poor and most vulnerable at greatest risk. It is expected that such section of society will become more exposed to climate shocks as a result of climate change. South Asia, and India in particular, is at high risk. India’s economy is closely linked to its natural resource base with over 700 million people in the country dependent on climate-sensitive livelihood sectors such as agriculture, water, and forestry that are further threatened by the impact of climate change (GoI 2008). These threats, however, will not be felt uniformly. Renewable freshwater already varies considerably across the country. With the growing hydro-climatic variability, much of India is expected to receive a larger volume of its precipitation during extreme rainfall events, such as in western and peninsular India, while other areas will experience fewer wet days, more dry days, and a heightened frequency of extreme events. Numerous options are emerging that are promising from an overall water resources perspective and provide greater resilience for those exposed to increasing climate-related risks. In this context, jointly with the Government of Bihar, International Water Management Institute (IWMI) and ICAR RCER are organizing one day workshop to discuss risk management solutions that promote better resilience among small and marginal farmers and vulnerable communities in promoting the advances in satellite technology and modeling tools through innovative risk transfer solutions involving insurance and drought monitoring to support preparedness as well as contingency plans for agricultural drought management.